ANALYSIS OF SOIL SUPPORTING FORCES (CASE STUDY OF BUILDING II MUHAMMADIYAH UNIVERSITY OF BIMA) - Junna, Isra; Najimudin, didin; Putra, B. Erdiansyah; Satriawansyah, Tri (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2023)
Bima City is one of the municipalities in West Nusa Tenggara, where the location is at the far end of the island of Sumbawa with hilly contours following the coastline, Muhammadiyah Bima University is a university that is growing rapidly in terms of students so it is very important to fulfill lecture facilities and infrastructure. The construction of Campus II Muhammadiyah University of Bima, which is a 5-storey building, of course, must be carefully planned for the carrying capacity of the soil due to the condition of the soil over land conversion from agricultural land to development which causes the soil's bearing force to be unstable. The sondir method is a technical step to determine the allowable depth of soil density so that it can determine the use of the type of foundation in the Bima Muhammadiyah University Building. From the results of the study of the carrying capacity of the soil for a depth range of more than 19.60 m with the highest Qc value of 83 Kg/Cm2, it is included in the category of soil with a permit carrying capacity. While the soil carrying capacity for a depth range of 19.80 m with a Qc value of 133 Kg/Cm2 is included in the rigid soil bearing capacity category.